Nanoengineering : global approaches to health and safety issues - Dolez, Patricia I. (Amsterdam : Elsevier, 2015)
Nanoengineering: Global Approaches to Health and Safety Issues provides a global vision on the impact of engineered nanomaterials both for the consumer/general public and in occupational settings. The book also presents a hint on what can be expected for the future from nanomaterials and their effects on our lives, both at home and at work. In addition, users will find valuable information on nanomaterials' irreplaceable value and their risks for health, safety, and environmental issues. Case studies illustrate key points and provide information on important processes.
14. INTRINSIC LIMITATIONS OF PREVIOUSLY DESCRIBED EXPERIMENTAL METHODS15. HOW TO SECURE NANOPOWDER PRODUCTION FACILITIES?; 16. WORLDWIDE INITIATIVES; 17. FUTURE TRENDS; 18. CONCLUSIONS; REFERENCES; Section 2 -- Consumer/General Public; Chapter 2.1 -- Public's Understanding, Perceptions, and Acceptance of Nanotechnology through the Lens of Consumer Products; 1. BACKGROUND/HISTORY OF THE PROJECT ON EMERGING NANOTECHNOLOGIES CONSUMER PRODUCTS INVENTORY; 2. PUBLIC UNDERSTANDING OF NANOTECHNOLOGY IN THE US HAS NOT CHANGED; 3. METHODOLOGY BEHIND THE CPI; 4. PITFALLS OF THE INVENTORY.
Online resource; title from PDF title page (Ebsco, viewed June 3, 2015).
Includes bibliographical references and index.
Keywords: Nanoparticles -- Health aspects; Nanoparticles -- Safety measures; Nanotechnology -- Health aspects; Nanotechnology -- Safety measures; SCIENCE / Nanoscience; TECHNOLOGY & ENGINEERING / Nanotechnology & MEMS; Nanostructures; Occupational Exposure -- prevention & control; Risk Management; Nanotechnology -- methods; Electronic books; Electronic books